Modernity and happiness: The case of Germany - Thomas Bulmahn (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2000)
The question asked in this paper is whether modern societies enable the individual to lead a happier life. It was hoped during the Age of the Enlightenment that rationally designed social conditions would lead in the future to greater prosperity, more security and increa- sed happiness for all. Only a little of this optimism has survived into the twentieth centu- ry. In their studies on anomie, sociologists such as Durkheim, Merton and Sennett have drawn attention to the darker sides of progress. Current theories of anomie – explicit social critiques – entirely ignore the successes of modernity and discuss only its crises. In these theories, anomie is described as a structural feature of modern societies, whose destructive consequences are manifested by growing alienation, increasing social isolati- on and rising suicidality. Empirical analyses of data from Germany show, however, that these theses diverge from the reality. Despite rapid processes of modernisation, anomic patterns of perception and behaviour have not become more widespread over the last 20 years; on the contrary, in some areas anomie has decreased significantly. Proceeding from this insight, this article proposes a correction of those models of anomie that are blind to progress. The crises of modernity are confronted with its successes, which have helped considerably to reduce anomic reactions and to stabilise subjective well-being at a high level. Finally, the article points out that this is not a stable equilibrium, rather that temporal and structural imbalances may occur in the course of modernisation processes, whose magnitudes may, however, be curbed – albeit not entirely or in every respect.
Keywords: 300; Sozialer Wandel; Soziale Werte; Lebensstandard; Öffentliche Meinung; Deutschland